Analysis of the Social Media Effect on Millennial Voter Participations in the 2019 Banda Aceh Legislative Elections - muhammad ilham; ubaidullah ubaidullah; ardiansyah ardiansyah (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
Social media is the main choice for the public in sharing various types of information massively. The ease of access and its targeted nature, then expands the role of social media which can actually be used for bigger interests, one of which is politics. The atmosphere of the 2019 General Election (Pemilu) can be used as an illustration of how social media has the power to spread political messages and invite voters, especially Beginner Voters who are very active in using various types of social media. Each candidate pair disseminates information through social media in the hope of getting support and sympathy. This study focuses on providing an overview of how social media is able to have a significant influence on communities participation, especially the Beginner Voters (Millennial Generation) in the 2019 Legislative Election, in Kecamatan Syiah Kuala, Baiturrahman and Kuta Alam as Top 3 (three) The Most Permanent Voters (DPT) in Banda Aceh. The approach with descriptive quantitative methods through the use of online survey instruments to the original Beginner Voters community from Banda Aceh was carried out in this study. Political Participation Theory and Persuasion Communication Model were used as research references which then resulted in the conclusion that Beginner Voters were active in using and using social media as the main source of information in finding references for political candidate choices. Furthermore, the Beginner Voters are the most influential voters in the race for votes, especially through campaigns on social media where they tend to choose partners who actively provide information through social media because they are considered attractive and easy to reach. Instagram is the main social media used by millennials to view political information.Keywords: Social Media, Beginner Voters, Legislative Election 2019.